Clinical Relevance of the LVEDD and LVESD Trajectories in HF Patients With LVEF < 35% - Chen, Yu-Chen; Hsing, Shi-Chue; Chao, Yuan-Ping; Cheng, Yung-Wen; Lin, Chin-Sheng; Lin, Chin; Fang, Wen-Hui (Frontiers in Medicine, 2022)
(1) Background: Certain variables reportedly are associated with a change in left ventricular ejection fraction (LVEF) in heart failure (HF) with reduced ejection fraction (HFrEF). However, literature describing the association between the recovery potential of LVEF and parameters of ventricular remodeling in echocardiography remains sparse. (2) Methods: We recruited 2148 HF patients with LVEF<35%. All patients underwent at least two echocardiographic images. The study aimed to compare LVEF alterations and their association with patient characteristics and echocardiographic findings. (3) Results: Patients with “recovery” of LVEF (follow-up LVEF≥50%) were less likely to have prior myocardial infarction (MI), had a higher prevalence of atrial fibrillation (Af), were less likely to have diabetes and hypertension, and had a smaller left atrium (LA) diameter, left ventricular end-diastolic diameter (LVEDD) and left ventricular end-systolic diameter (LVESD), both in crude and in adjusted models (adjustment for age and sex). LVEDD cutoff values of 59.5 mm in men and 52.5 mm in women and LVESD cutoff values of 48.5 mm in men and 46.5 mm in women showed a year-to-year increase in the rate of recovery (follow-up LVEF≥50%)/improvement (follow-up LVEF≥35%), p value<0.05 in Kaplan–Meier estimates of the cumulative hazard curves. (4) Conclusions: Our study shows that LVEDD and LVESD increments in echocardiography can be predictors of changes in LVEF in in HF patients with LVEF<35%. They may be used to identify patients who require more aggressive therapeutic interventions.